Innovacionnaja tehnologija komp'juternogo testirovanija psihomotoriki v sportivnyh igrah - Lisenchuk, G.; Tyshchenko, V. (Science in Olympic Sport, 2019)
Objective. To test experimentally the effectiveness for the use of the innovative computer program in the training process of team sports. Methods. Analysis of scientific and methodical literature, pedagogical observations and experiments and methods of mathematical statistics. Results. Currently, there are the well-developed theory and methods of pedagogical control in sport and the system of integrated control in some sports. The charges increased demands on the organization of measures to ensure the control and management of the training process determines the need to develop new tools, techniques and technologies that allow the trainer to receive and process a large amount of diverse information. The modern control system should be based on the postulate of the impossibility of evaluation of integrated systems of the human body on the basis of data on the individual components. The computer program is designed to calculate the assessment of the level of theoretical knowledge and tactical thinking in team sports, to save the results for the viewing of dynamics. The proposed method of the assessment test of psychophysical qualities for athletes makes it possible to quantify the speed of switching attention of the athlete in the condition of active selection of useful information, its thorough analysis and making timely decisions, that would contribute to signifi cantly improve the effi ciency of competitive activity. Analyzing the dynamics of the level in theoretical knowledge for our research of futsal athletes, Pearson criterion was 4.27 si.u.; athletes of handball team - 26.93 si.u.; players of basketball team - 7.81 si.u. Pearson criterion of the level of tactical thinking of the initial and fi nal data for futsal team athletes made 12.61 si.u.; players of handball team - 32.37 si.u.; athletes of basketball team - 8.14 si.u. Conclusion. It is possible to state that handball helps more rapid, speedy and expedient flow of thoughts processes aiming to find efficient ways to solve problems and achieve goals and to develop a sense of extrapolation of technical actions that occurs during the game.